Robustness of carbon nanotube-based sensor to probe composites' interfacial damage in situ. (January 2016) - Pillin, Isabelle; Castro, Mickael; Nag Chowdhury, Suvam; Feller, Jean-Francois
A carbon nanotube-based sensing interphase, acting as a quantum resistive sensor, has been homogenously integrated in glass fibres–epoxy composites to investigate their interfacial damage in situ. Depending on the chemical constitution of the transducer, the strain monitoring of composites via quantum resistive sensor can be limited to the elastic domain of deformation over which it is progressively destroyed, or it can allow collecting information on the damage in the nonlinear range. Combined macro- and micromechanical tests on composites with quantum resistive sensor interphase appear helpful to develop smart composites with health monitoring capability.